Calicivirus VP2 Forms A Portal-like Assembly Following Receptor Engagement - Michaela J. Conley; Marion McElwee; Liyana Azmi; Mads Gabrielsen; Olwyn Byron; Ian G. Goodfellow; David Bhella (Nature Publishing Group, 2024)
Indexed by ERA